Differential roles of human striatum and amygdala in associative learning - Li, Jian (2011)
Although the human amygdala and striatum have both been implicated in associative learning, only the striatum’s contribution has been consistently computationally characterized. Using a reversal learning task, we demonstrate that amygdala BOLD activity tracks associability as estimated by a computational model, and dissociates it from the striatal representation of reinforcement prediction error. These results extend the computational learning approach from striatum to amygdala, demonstrating their complementary roles in aversive learning.